Caracterización del Perfil Hematológico y Bioquímico de la Trucha Silvestre Ecuatoriana en la Provincia de Cotopaxi y Bioquímico de la Trucha Silvestre Ecuatoriana en la Provincia de Cotopaxi. - Cárdenas Moncayo, Carlos Enrique. (2018)
The present investigation was carried out in the Cotopaxi Province, Latacunga Canton, in the Limpiopungo y Salayambo moors as well as in the Salcedo Canton in Cusubamba moors, for the characterization of the hematological and biochemical profile of the Ecuadorian wildlife trout (Oncorhynchus mykiss). A total of thirty species were captured, in the wild, to proceed with the sample collection by puncture through the caudal vein, one ml of blood was taken in a minicooler tubes of lilac cap for the hematological profile and two ml of blood in a vacoutainer tubes of red cap for the biochemical profile, the samples were transported to San Francisco Clinical Laboratory in the Ambato city. Once the results were obtained and the tabulations were done in the Excel program. The descriptive analysis was used to evaluate the average of all the parameters, which were the following: for the hematological profile the values are Hematocrit (%) 40.95, Hemoglobin (g/L) 13.07, Erythrocytes (mm3) 4,397,333.33, Average glomerular volume (fl) 94.06, Average corpuscular hemoglobin (pg) 29.94, Average Concentration of corpuscular hemoglobin (g/dL) 31.86, Platelets (mm3) 33700 in the leucogram, the following values were obtained: Leukocytes (mm³) 14540, Neutrophils (%) 15.53 Lymphocytes (%) 78.40, Monocytes (%) 6.03, Eosinophils (%) 0, Basophils (%) 0 and for the biochemical profile the values obtained were: Glucose (mmol/L) 4.38, Urea (mmol/L) 2.36, BUN (mmol/L) 1.08, Creatinine (umol/L) 40.92, AST (U/L) 152.99, ALT (U/L) 97.28, Total Proteins (g/L ) 38.25, Calcium (mmol/L) 5.06, Phosphorus (mmol/L) 7.44, Potassium (mmol/L) 24.84. The data obtained in this investigation were different from those of previous literatures, especially the hematocrit, which was high in relation to other studies. The clarification of this event is that the animals were studied at a height higher than 3000 m.a.s.l but having agreement in the absence of eosinophils and basophils.